Evaluation of the Effect of “Honey Zufa” Herbal Syrup on Cough in Hospitalized Patients With COVID-19: A Double Blind Randomized Clinical Trial - Marziyeh Heydari; Hossein Kazemi Zadeh; Soha Namazi; Hamid Emadi Koochak; Nasim Khajavi Rad; Mahnaz Khanavi; Arman Zargaran (Acta Medica Iranica)
Cough is one of the most prevalent symptoms of COVID-19, affecting over 60% of patients. This symptom significantly diminishes quality of life, causing fatigue, insomnia, dysphonia, musculoskeletal pain, and urinary incontinence. Honey Zufa herbal syrup is a well-known antitussive remedy in the Iranian market and was evaluated for its potential to alleviate this symptom. This study aimed to assess the efficacy and safety of Honey Zufa herbal syrup in treating acute cough resulting from mild to moderate COVID-19. A randomized controlled trial was conducted with 200 patients assigned to either the treatment group, receiving Honey Zufa herbal syrup, or the placebo group, receiving a placebo. Both groups also received standard cough control medications. Cough severity was measured using three different scoring systems. The impact of Honey Zufa on cough severity, the influence of other medications, and changes in laboratory parameters were monitored over a 14-day period. Honey Zufa herbal syrup significantly reduced cough severity compared to the placebo across all scoring systems. The treatment group experienced a greater reduction in cough severity than the placebo group. However, there was no significant difference between the groups in terms of antitussive medication regimens. Laboratory parameters remained stable, and no significant side effects were observed. Honey Zufa herbal syrup effectively reduces cough severity in patients with mild to moderate COVID-19, suggesting it could serve as a useful complementary and alternative treatment option for COVID-19-induced cough.